Influence of deficit irrigation and nano NK application on root dynamics, physiology and WUE of transplanted rice (Oryza sativa) - VASUKI, A; PAULPANDI, V K; GURUSAMY, A; SIVAKUMAR, T; PRABAKARAN, K (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during the rainy (kharif) (June–September, 2022) and winter (rabi) (December 2022–March, 2023) seasons at Agricultural College and Research Institute (Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu), Madurai, Tamil Nadu to study the effect of irrigation methods and nutrient management strategies on the growth of roots, physiological aspects, yield and water use efficiency of transplanted rice (Oryza sativa L.). Experiment was conducted in a split-plot design comprised of 3 irrigation methods, viz. Irrigation at 15 cm depletion of water level in field water tube (M1); Alternate wetting and drying (M2); Conventional flooding (M3) in main plot and 7 nutrient management strategies, viz. Application of 50% N + nano urea as foliar spray (S1); 75% N + nano urea as foliar spray (S2); 50% K + nano potash as foliar spray (S3); 75% K + nano potash as foliar spray (S4); 50 and 75% N and K + nano urea and potash as foliar spray (S5); 100% RDF (S6); and absolute control (S7) in sub plot, replicated thrice. Results indicated that under M1S2, root characteristics like length, volume and dry weight were notably higher. Physiological attributes such as stomatal conductance, transpiration and photosynthetic rate recorded high with M2S5. However, the maximum yield and water use efficiency were observed with M2S5. In conclusion, the treatment combination M2S5 is considered as practical recommendation for farmers in the Periyar Vaigai command area, ensuring optimal yield while economically utilizing water and fertilizers.